Exploring the pattern and neural correlates of neuropsychological impairment in late-life depression. - Sexton, C; McDermott, L; Kalu, U; Herrmann, L; Bradley, K; Allan, C; Le Masurier, M; Mackay, C; Ebmeier, K (2012)
BACKGROUND: Neuropsychological impairment is a key feature of late-life depression, with deficits observed across multiple domains. However, it is unclear whether deficits in multiple domains represent relatively independent processes with specific neural correlates or whether they can be explained by cognitive deficits in executive function or processing speed. METHOD: We examined group differences across five domains (episodic memory; executive function; language skills; processing speed; visuospatial skills) in a sample of 36 depressed participants and 25 control participants, all aged ≥ 60 years. The influence of executive function and processing speed deficits on other neuropsychological domains was also investigated. Magnetic resonance imaging correlates of executive function, processing speed and episodic memory were explored in the late-life depression group. RESULTS: Relative to controls, the late-life depression group performed significantly worse in the domains of executive function, processing speed, episodic memory and language skills. Impairments in executive function or processing speed were sufficient to explain differences in episodic memory and language skills. Executive function was correlated with anisotropy of the anterior thalamic radiation and uncinate fasciculus; processing speed was correlated with anisotropy of genu of the corpus callosum. Episodic memory was correlated with anisotropy of the anterior thalamic radiation, the genu and body of the corpus callosum and the fornix. CONCLUSIONS: Executive function and processing speed appear to represent important cognitive deficits in late-life depression, which contribute to deficits in other domains, and are related to reductions in anisotropy in frontal tracts.